Concrete anti-impact wear-resistant agent, and preparation method and application thereof

By using alkali-cooking-ion-exchange combination materials of tungsten slag, ultrafine limestone powder and fly ash float beads in concrete in high altitude and high cold areas, the problems of impact wear performance and heavy metal pollution in concrete in high cold areas are solved, and the problem of concrete resistance and wear resistance and heavy metal pollution in high cold areas is achieved. It has efficient compressive strength and wear resistance, reduced viscosity and pollution risks, and is suitable for the construction of high-dam flood discharge systems.

CN119285260APending Publication Date: 2025-01-10POWERCHINA ZHONGNAN ENG +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411083161.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The concrete high dams in high altitude and cold areas in flood discharge systems caused by surface cracking and strength reduction due to the erosion and abrasion of water flow and sand and gravel. The existing methods use active mineral blends such as silicon powder to improve impact wear performance but bring hydration. The risk of temperature rise and cracking, and the tungsten slag contains heavy metal contamination, a material that can not only improve impact wear performance but also cure heavy metals.

Method used

Tungsten slag, ultrafine limestone powder and fly ash beads generated by alkali cooking-ion exchange method are used as the main materials. By controlling the particle fineness and proportion of the material, a new type of concrete impact-resistant wear resistance is developed, through tungsten Slag powder improves impact wear performance, ultrafine limestone powder and fly ash float beads reduce viscosity, combined with the dual-motion mixing mechanism, it is appropriately incorporated into concrete to improve compressive strength and wear resistance.

Benefits of technology

It has achieved the improvement of the compressive strength and wear resistance of concrete in high altitude and high cold areas, reduced the viscosity of concrete, avoided the pollution of heavy metals in tungsten slag, met the construction requirements of the high dam flood discharge system, and was low in cost, comply with the environmental protection strategy. .

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a concrete anti-impact and anti-wear agent as well as a preparation method and application thereof. The concrete anti-impact and wear-resistant agent is prepared by taking tungsten slag generated by tungsten smelting through an alkali boiling-ion exchange method, superfine limestone powder and fly ash floating beads as main materials, controlling the particle fineness and particle gradation combination of the three materials and designing a reasonable ratio. The tungsten slag generated by tungsten smelting through an alkali boiling-ion exchange method is adopted as a main component, waste is utilized, the cost is low, and meanwhile cement in concrete can be used for curing and locking harmful heavy metal ions in the tungsten slag; according to the concrete anti-abrasion agent, the mechanical strength and anti-abrasion performance of a concrete gel system are improved by utilizing the wood characteristic of high hardness of the tungsten slag, meanwhile, the accumulation state of powder particles is improved by utilizing the morphological characteristics and micro-grading characteristics of the superfine limestone powder and the fly ash floating beads, so that the viscosity of concrete is effectively reduced, the workability is high, the cracking risk is low, and the service life of the concrete is prolonged. The method is suitable for high-altitude alpine regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete admixtures, and in particular to an anti-impact and anti-wear agent for concrete used in high-altitude and cold areas and applications thereof. Background Art

[0002] The special climatic conditions in high-altitude and cold areas pose severe challenges to the safe operation of concrete high dams. The concrete of the concrete high dam flood discharge system building is eroded and abraded by water flow and the sand and gravel it carries all year round, resulting in cracking, damage and strength reduction of the concrete surface. For this reason, hard aggregates (such as basalt aggregates, iron ore sand and gravel aggregates, cast stone aggregates, etc.) are often used as aggregates for anti-abrasion concrete to improve the anti-abrasion performance of concrete. However, when these hard aggregates are lacking around the dam site, it is necessary to improve the anti-abrasion strength from the perspective of improving the anti-abrasion performance of the concrete cementitious system. At present, the main method to improve the performance of the cementitious material system is to add active mineral admixtures such as silica powder. While improving the mechanical strength of the cementitious system through active mineral admixtures, it also brings about the disadvantages of increased hydration temperature rise, increased shrinkage deformation, and increased cracking risk of the cementitious system; therefore, improving the anti-abrasion performance of concrete in the high dam flood discharge system building is a difficult and hot issue that needs to be solved urgently.

[0003] Tungsten is a precious rare metal with the characteristics of high melting point, high density and high hardness. It has stable chemical properties at room temperature and is corrosion-resistant. It is mainly used to produce alloy steel and hard alloy. Alkali boiling-ion exchange method is one of the tungsten smelting processes. At present, this process has become the mainstream process for the production of ammonium paratungstate (APT) in my country. A large amount of solid waste is generated in the APT production process - tungsten slag produced after alkali boiling of tungsten concentrate; As and Pb heavy metals associated with tungsten concentrate eventually enter the tungsten slag. A large amount of tungsten slag is piled up in the open air or used in an uncontrolled manner, which will cause serious pollution to the surrounding soil and surface water. Studies have shown that cement has the natural advantage of solidifying heavy metals such as As and Pb, and tungsten slag has the characteristic of high hardness due to the high content of tungsten. Therefore, the development of high dam anti-abrasion concrete anti-abrasion agent based on tungsten slag has inherent advantages, which can solve the problem of solidification of harmful heavy metals in tungsten slag and improve the anti-abrasion performance of anti-abrasion concrete by using the high hardness of tungsten slag. It is a solid waste eliminated in the production of ammonium paratungstate, and the metal elements contained in it make the tungsten slag have a greater hardness. The characteristics of high hardness and high wear resistance make tungsten slag used as concrete aggregate to improve the compressive strength and wear resistance of concrete. Some components in tungsten slag make it water-absorbent. Under the combined effect of factors such as large surface area and good interface bonding with cement paste, the addition of tungsten slag will increase the viscosity of concrete and have an adverse effect on the fluidity of concrete. Therefore, in addition to tungsten slag, a concrete viscosity reducer is added to ensure that the impact and wear resistance agent has good fluidity while improving the impact and wear resistance of concrete. Summary of the invention

[0004] In view of the problems in the above background technology, the present invention provides a new type of concrete anti-impact and wear-resistant agent for high-altitude and cold areas and its preparation method. The present invention uses tungsten slag produced by tungsten smelting by alkali boiling-ion exchange method, ultrafine limestone powder, and fly ash floating beads as main materials, and develops a new type of concrete anti-impact and wear-resistant agent by controlling the particle fineness and particle grading combination of the above three materials and designing a reasonable ratio.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] A concrete anti-impact and wear-resistant agent, comprising component A and viscosity-reducing component B, wherein component A is tungsten slag powder, and viscosity-reducing component B comprises ultrafine limestone powder and fly ash floating beads, and the mass percentages of the components are as follows:

[0007] Tungsten slag powder 55%~75%,

[0008] Ultrafine limestone powder 5% to 15%,

[0009] Fly ash floating beads 10% to 30%;

[0010] Among them, the function of tungsten slag powder is to improve the impact and abrasion resistance of concrete, and the function of component B obtained by mixing ultrafine limestone powder and fly ash floating beads in a certain proportion is to reduce the viscosity of concrete, and the mass percentage of viscosity-reducing component B is in the range of 25% to 45%;

[0011] The tungsten slag powder is a tungsten slag powder with a fineness of 7% to 10% of the residue on a 45 μm sieve, which is obtained by grinding the tungsten slag produced by tungsten smelting by an alkali boiling-ion exchange method through an air flow mill;

[0012] The ultra-fine limestone powder has a fineness of 200-400 mesh (referred to as "stone powder"), which is obtained by grinding limestone powder through an air flow mill;

[0013] The fly ash floating beads have a fineness of 100-150um (referred to as "floating beads").

[0014] Furthermore, the present invention also provides a method for preparing the above-mentioned concrete anti-impact and wear-resistant agent, comprising: mixing three raw materials of tungsten slag powder, ultrafine limestone powder and fly ash floating beads by using a double-motion mixer to prepare the anti-impact and wear-resistant agent;

[0015] The parameters of the mixer when in use are: vibration frequency 20-30 Hz, rotation speed 15-20 r / min, mixer worktable inclination 10°-15°, and mixing time 2h-4h.

[0016] Furthermore, the present invention also provides an application method of the above concrete impact and wear resistant agent. When the concrete impact and wear resistant agent is added to concrete, it is added at 10% to 20% of the mass of the cementitious material in the concrete containing the impact and wear resistant agent.

[0017] Through the above technical scheme, this application starts from the hardness characteristics of tungsten slag and adopts tungsten slag powder with specific fineness and mixing ratio as the main component of concrete anti-impact and wear-resistant agent, which can improve the wear resistance of the cementitious system in concrete. At the same time, cement can also solidify heavy metals such as As and Pb in tungsten slag powder to prevent the heavy metals of tungsten slag powder from overflowing; stone powder can improve the micro-grading and enhance the density between cement, tungsten slag powder and other particles by virtue of its surface and particle morphology, thereby improving the workability of anti-impact and wear concrete mixture; floating beads can improve the powder gap between tungsten slag powder, stone powder and floating beads due to their spherical morphology, and at the same time play the role of "ball bearings" between cementitious materials, reduce water consumption, and exert the "micro-aggregate effect" to improve the stacking state between powder particles, further play a water-reducing role, thereby effectively reducing the viscosity of concrete.

[0018] When the concrete anti-impact and wear-resistant agent of the present invention is added to concrete, referring to the detection method of "Concrete Expansion Agent" GB / T23439-2017, the 7d compressive strength of the concrete reaches above 30MPa, the 28d compressive strength reaches 50MPa, and the 7d limited expansion rate in water is ≥0.050%, reaching or even exceeding the performance requirements of the specification.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention adopts tungsten slag produced by tungsten smelting by alkali boiling-ion exchange method as the main component, which is waste utilization with low cost, conforms to the national strategic policy, and has significant economic and social significance; the concrete anti-impact and wear-resistant agent of the present invention is used in concrete and has good anti-impact and wear properties.

[0021] (2) Compared with the prior art, the concrete anti-abrasion agent of the present invention utilizes the material characteristics of high hardness of tungsten slag to improve the mechanical strength and anti-abrasion performance of the concrete cementitious system, and at the same time utilizes the morphological characteristics and micro-grading characteristics of ultra-fine limestone powder and fly ash floating beads to improve the stacking state between powder particles, thereby effectively reducing the viscosity of concrete. It has high construction quality and low cracking risk, and is suitable for high-altitude and cold areas. There is no need to add special concrete viscosity-reducing products, thereby saving the manufacturing cost of anti-abrasion concrete. DETAILED DESCRIPTION

[0022] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form.

[0023] The concrete anti-impact and wear-resistant agent of the present invention comprises component A and viscosity-reducing component B, wherein component A is tungsten slag powder, and viscosity-reducing component B comprises ultrafine limestone powder and fly ash floating beads, and the mass percentages of the components are as follows:

[0024] Tungsten slag powder 55%~75%,

[0025] Ultrafine limestone powder 5% to 15%,

[0026] Fly ash floating beads 10% to 30%;

[0027] Among them, the function of tungsten slag powder is to improve the impact and abrasion resistance of concrete, and the function of component B obtained by mixing ultrafine limestone powder and fly ash floating beads in a certain proportion is to reduce the viscosity of concrete, and the mass percentage of viscosity-reducing component B is in the range of 25% to 45%;

[0028] The tungsten slag powder is a tungsten slag powder with a fineness of 7% to 10% of the residue on a 45 μm sieve, which is obtained by grinding the tungsten slag produced by tungsten smelting by an alkali boiling-ion exchange method through an air flow mill;

[0029] The ultra-fine limestone powder has a fineness of 200-400 mesh (referred to as "stone powder"), which is obtained by grinding limestone powder through an air flow mill;

[0030] The fly ash floating beads have a fineness of 100-150um (referred to as "floating beads").

[0031] Furthermore, the present invention also provides a method for preparing the above-mentioned concrete anti-impact and wear-resistant agent, comprising: mixing three raw materials of tungsten slag powder, ultrafine limestone powder and fly ash floating beads by using a double-motion mixer to prepare the anti-impact and wear-resistant agent;

[0032] The parameters of the mixer when in use are: vibration frequency 20-30 Hz, rotation speed 15-20 r / min, mixer worktable inclination 10°-15°, and mixing time 2h-4h.

[0033] Example 1

[0034] A concrete anti-impact and wear-resistant agent, the raw materials include the following components in terms of mass percentage:

[0035] Component A contains 72% tungsten slag powder and 28% viscosity-reducing component B, of which the mass percentage of stone powder and the mass percentage of floating beads in the viscosity-reducing component is 13% and 15% respectively;

[0036] The fineness of the tungsten slag powder is 9% on a 45 μm sieve, the fineness of the ultrafine limestone powder is 200 meshes, and the fineness of the fly ash floating beads is 150 μm.

[0037] The preparation method of the concrete anti-impact and wear-resistant agent comprises the following steps: using a double-motion mixing device to mix components A and B, controlling the mixer vibration frequency to 25 Hz, the speed to 17 r / min, the mixer worktable inclination to 12°, and the mixing time to 3 hours. Furthermore, after the mixing is completed, component C is the novel concrete anti-impact and wear-resistant agent of the invention, and all steps are completed at room temperature.

[0038] Example 2

[0039] The difference between Example 2 and Example 1 is: a concrete anti-impact and wear-resistant agent, wherein the components and their mass percentages are as follows: component A tungsten slag powder 63%, viscosity reducing component B content 37%, wherein the mass percentage of stone powder is 15%, and the mass percentage of floating beads is 22%; the fineness of the tungsten slag powder is 9% on a 45μm sieve, the fineness of the ultrafine limestone powder is 300 mesh, and the fineness of the fly ash floating beads is 150um.

[0040] Example 3

[0041] The difference between Example 3 and Example 1 is: a concrete anti-impact and wear-resistant agent, wherein the components and their mass percentages are as follows: component A tungsten slag powder 66%, viscosity reducing component B content 34%, wherein the mass percentage of stone powder is 7%, and the mass percentage of floating beads is 27%; the fineness of the tungsten slag powder is 9% on a 45μm sieve, the fineness of the ultrafine limestone powder is 300 mesh, and the fineness of the fly ash floating beads is 250um.

[0042] Comparative Example 1

[0043] The difference between Comparative Example 1 and Example 1 is that component A in the impact and wear resistant agent is unmilled tungsten slag.

[0044] Comparative Example 2

[0045] The difference between Comparative Example 2 and Example 1 is that a single tungsten slag powder is used in the impact and wear resistant agent, and the viscosity reducing component B is not added.

[0046] Comparative Example 3

[0047] The difference between Comparative Example 3 and Example 2 is that the content of tungsten slag powder of component A in the impact and wear resistant agent is relatively high, which is 80%, and the viscosity reducing component B is 20%, of which stone powder is 14% and fly ash floating beads are 6%.

[0048] Comparative Example 4

[0049] The difference between Comparative Example 4 and Example 2 is that the content of tungsten slag powder of component A in the impact and wear resistant agent is relatively low, at 45%, the content of viscosity reducing component B is 55%, of which the content of stone powder is 23% and the content of fly ash floating beads is 32%.

[0050] Comparative Example 5

[0051] The difference between Comparative Example 5 and Example 3 is that the fineness of the components in the impact and wear resistant agent is different, wherein the fineness of tungsten slag is 45 μm with a sieve residue of 20%, the fineness of stone powder is 100 mesh, and the fly ash floating beads are 400 μm.

[0052] Blank example

[0053] In the blank example, no impact and wear resistant agent was added to replace cement, and the dosage of component C was 0.

[0054] The performance tests of the embodiments of the present invention and the comparative examples were measured according to the requirements and test methods specified in "Concrete Expansion Agent" (GB / T 23439-2017) and "Standard for Performance Test Methods of Ordinary Concrete Mixtures" (GB / T 50080-2016). The cement used was P·O 42.5 grade ordinary silicate cement, the sand used was standard sand that met the requirements of GB / T 23439-2017, and the test water was tap water. During the test, the amount of concrete anti-impact and wear-resistant agent accounted for C% of the mass of concrete cementitious materials. The test results are shown in the table below.

[0055] Table 1 Performance comparison of various embodiments and comparative examples

[0056] Example No. Dosage C% 7d compressive strength / MPa 28d compressive strength MPa 7d limited expansion rate in water % Slump / mm Example 1 10 32.8 52.6 0.081 70 Example 2 15 36.1 55.3 0.079 65 Example 3 20 35.0 54.7 0.086 65 Comparative Example 1 10 30.8 50.1 0.071 70 Comparative Example 2 10 31.2 50.8 0.037 60 Comparative Example 3 15 32.3 52.1 0.076 60 Comparative Example 4 15 30.6 51.8 0.078 60 Comparative Example 5 20 28.9 49.0 0.070 55 Blank example 0 26.7 47.9 0.027 70

[0057] GB / T 23439-2017 "Concrete Expansion Agent" requires that the 7d compressive strength reaches 22.5MPa or more, the 28d compressive strength reaches 42.5MPa, and the 7d limited expansion rate in water is ≥0.050%. It can be seen from the test results of the embodiment that the cement mortar mixed with the impact and wear resistant agent of the present application has excellent mechanical properties, and its strength value reaches or even exceeds the required performance of the specification, and its 7d compressive strength reaches 30MPa or more, and the 28d compressive strength reaches 50MPa.

[0058] Combining the performance of the blank example, comparative examples 1-5 and embodiments 1-3, it can be known that the powder fineness, dosage and viscosity-reducing component content of the tungsten slag play a very important role in the mechanical properties of the concrete anti-impact and wear-resistant agent of the present invention in concrete. When the fineness of the tungsten slag powder is 7% to 10% on a 45μm sieve, accounting for 55-75% by mass, the fineness of the ultrafine limestone powder is 200 mesh to 400 mesh, accounting for 5% to 15% by mass, and the fineness of the fly ash beads is 100-150um, accounting for 10% to 30% by mass, the performance test of the anti-impact and wear-resistant agent is relatively excellent, and the viscosity of the concrete is basically equivalent to that of the blank example, and the slump of the concrete is in the range of 50mm to 70mm, which meets the requirements for the slump of the mixture in the construction of anti-impact and wear concrete in high-altitude and cold areas.

Claims

1. A concrete anti-impact and wear-resistant agent, characterized in that: It includes component A and viscosity-reducing component B. Component A is tungsten slag powder, and viscosity-reducing component B includes ultrafine limestone powder and fly ash floating beads. The mass percentage of each component is as follows: Tungsten slag powder 55%~75%, Ultrafine limestone powder 5% to 15%, Fly ash floating beads 10% to 30%; and the mass percentage of the viscosity reducing component B is in the range of 25% to 45%; The fineness of the tungsten slag powder is 7% to 10% with a 45um sieve residue; The ultrafine limestone powder has a fineness of 200-400 mesh; The fly ash floating beads have a fineness of 100-150um.

2. A concrete anti-impact and wear-resistant agent according to claim 1, characterized in that: The tungsten slag powder is obtained by grinding tungsten slag produced by tungsten smelting by alkali boiling-ion exchange method through an air flow grinder.

3. A concrete anti-impact and wear-resistant agent according to claim 1, characterized in that: The ultrafine limestone powder is obtained by grinding limestone powder through an air flow mill.

4. The method for preparing a concrete impact and wear resistant agent according to any one of claims 1 to 3, characterized in that: include: The impact and wear resistant agent is prepared by mixing three raw materials, tungsten slag powder, ultrafine limestone powder and fly ash floating beads, using a double-motion mixer; The parameters of the mixer when in use are: vibration frequency 20-30 Hz, rotation speed 15-20 r / min, mixer worktable inclination 10°-15°, and mixing time 2h-4h.

5. The application method of the concrete anti-impact and wear-resistant agent according to any one of claims 1 to 3, characterized in that: It is applied in concrete. When it is added into concrete, it is added at 10% to 20% of the mass of cementitious materials in the concrete containing the impact and wear resistant agent.

6. The application method according to claim 5, characterized in that: When the cementitious material is added into the concrete at a rate of 10% to 20% of the mass of the concrete, referring to the test method of "Concrete Expansion Agent" GB / T 23439-2017, the compressive strength of the concrete shall reach above 30MPa at 7d and 50MPa at 28d, and the limited expansion rate in water at 7d shall be ≥0.050%.